Biomotor Dimensions: Analysis Of Basketball Skills In Students (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The study aimed to analyze biomotor components in relation to basketball skills among students at Mardi Rahayu Ungaran Junior High School. A quantitative approach with descriptive analysis was applied to 120 seventh and eighth grade students selected through purposive sampling. Measurements included biomotor tests such as ball throwing and catching, push-ups, beep tests, and basketball skills measured by dribbling, passing, and shooting tests. The data were analyzed descriptively. The results of the analysis showed that the average score for throwing and catching was 7.48±6.89, the average for push-ups was 14.48±4.66, an average beep test score of 24.76±1.45, an average dribbling skill score of 17.50±7.50, a passing skill score of 16.12±6.74, and a shooting skill score of 0.83±1.35. The results showed that the majority of biomotor components were in the adequate to poor category, while basic basketball skills were generally in the poor to very poor category, especially shooting skills, which were very low. The findings show a close relationship between suboptimal biomotor conditions and poor mastery of basic basketball techniques. The conclusion of this study emphasizes the need for a programmed PE learning intervention to improve biomotor components as the basis for improving basketball skills.